2023
DOI: 10.1523/eneuro.0007-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Data Resource and Benchmarks for Time Cell Analysis and Detection Algorithms

Abstract: Hippocampal CA1 cells take part in reliable, time-locked activity sequences in tasks that involve an association between temporally separated stimuli, in a manner that tiles the interval between the stimuli. Such cells have been termed time cells. Here we adopt a first-principles approach to comparing diverse analysis and detection algorithms for identifying time cells. We generated synthetic activity datasets using calcium signals recordedin vivofrom the mouse hippocampus using 2-Photon imaging, as template r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Time cells, defined as neurons that fire consistently at the same time relative to the CS onset across trials, were identified using a custom C++ code (Ananthamurthy and Bhalla, 2023). This code employs two algorithms to detect time cells: the ridge to background method (Modi et al, 2014) and the temporal information method (Mau et al, 2018b).…”
Section: Time Cell Detectionmentioning
confidence: 99%
“…Time cells, defined as neurons that fire consistently at the same time relative to the CS onset across trials, were identified using a custom C++ code (Ananthamurthy and Bhalla, 2023). This code employs two algorithms to detect time cells: the ridge to background method (Modi et al, 2014) and the temporal information method (Mau et al, 2018b).…”
Section: Time Cell Detectionmentioning
confidence: 99%